Aplikasi Penginderan Jauh dan Sig Untuk Penetapan Tingkat Kemampuan Penggunaan Lahan (KPL) (Studi Kasus di DAS Nawagaon Maskara, Saharanpur-India) - Harjadi, Beny (Forum Geografi, 2007)
The land that was increasingly crowded resulting from the inhabitantsâs speeding-up pressure, required the utilisation of the land to be as efficient and as effectively as possible. For this matter must be known by the LUC (Land Use Capability) class respectively the unit of the land management, so as to be known as early as possible the obstacle factor from the land and could be done by the utilisation of the land as optimally as possible. The implementation of the LUC determination must be carried out a stage for the sake of a stage by counting LUC respectively the main factor, so as to be received by LUC-Soil, LUC-Erosion, and LUC-Slope. The next one of the three of this LUC were just counted by the value of the maximum to appoint LUC Final. LUC-Slope by being based on the Wischmeier and Smith (1978), LUC-Erosion was counted by using the quantitative MMF erosion formula (Morgan, Morgan, and Finney), and LUC-Soil by gathering the physical data the field took the form of the texture data of the land, drainage, solum and the percentage of the rock in the surface. LUC-Erosion and LUC-Soil were received by 5 LUC classes (I, II, III, IV, IV, and VI), whereas LUC-Slope was received by 7 LUC classes all of them except the V. LUC I class until IV were recommended for the agricultural crop and LUC V until VIII for the forestry crop. From 11 of Sub Watershed LUC VIII was expanded 107.54 ha to Sub Watershed Sarbar Rao and narrowest to Sub Watershed Maskara Rao (0.12 ha). On the other hand for LUC II was expanded to Sub Watershed Nawagaon Rao (1136.8 ha) and narrowest (1.51 ha) to Sub Watershed Shakumbari Rao. The location of the research in Sub Watershed Nawagaon Rao Mascara the Saharanpur city, India, with the location goegrafis from 30 o 09â 00" N - 30o 21â 00" N and longitude 77 o 34â 00" E - 77 o 51â 00" E, widely the Watershed whole 205.94 km2 or 20594.49 ha. The analysis of the image satelit with IRS (Indian Remote Sensing) LISS IV in January 2005, the analysis of three dimensions with DEM SRTM, and the map of the topography of the sheet 53 F/11, 53 F/12, 53 F/15 and 53 F/16. The aim of the research of determining the LUC class by counting each one of LUC-Soil, LUC-Erosion, and LUC-Slope. The use of the land in the Nawagaon Maskara Rao Watershed in part: Wheat super (969,26), normal Wheat (2753.7 ha), the Orchard (2103.2 ha), the Forest was rather close (3930.5 ha), the Forest was open (3352.1 ha), Scrub (168.62 ha), Brush rocky (658.56 ha), and Open land (1814.8 ha). Was based on results of this research recomendation for LUC VIII was only for the protected forest that might not be touched or produced.